The removal of natural organic matter with LiCl–TiO2-doped PVDF membranes by integration of ultrafiltration with photocatalysis - Song, Hongchen; Shao, Jiahui; Wang, Jianming; Zhong, Xiaoqing (Desalination, 2014)
Ultrafiltration has become one of the best alternatives replacing conventional drinking water treatment technologies because of increasing stringent regulations for drinking water quality. However, membrane fouling is an important factor which restricts its widespread application. In this study, the modified polyvinylidene fluoride (PVDF) membranes were prepared by adding different amounts of LiCl and TiO2 particles. The performances of PVDF–LiCl membranes and PVDF–LiCl–TiO2 membranes were investigated by discussing the rejection of natural organic matter (NOM) and flux decline in both dead-end and cross-flow filtration experiments. The effect of photocatalytic degradation on TiO2-doped PVDF membranes was also evaluated. Results from both this study and the previous one with the membrane prepared by adding organic addition agent PEG and TiO2 photocatalyst indicated that appropriate TiO2-doped modification on PVDF membrane could be an effective way for better NOM rejection and reduction of membrane fouling at the same time. TiO2-doped PVDF membrane also shows good self-cleaning ability. The fouled membrane can be cleaned with irradiation and the foulants' photocatalytic degradation is most effective in the first 30min. •Adding TiO2 to PVDF–LiCl improves membrane hydrophilicity, smoothness and rejection.•TiO2-doped PVDF membrane has a good self-cleaning ability.•Optimum irradiation time should be considered to offer the self-cleaning property.•UV irradiation might be a method of membrane cleaning for photocatalytic membranes.